Development of integument and cutaneous glands in larval, juvenile and adult toads (Rhinella granulosa): a morphological and morphometric study. (31st July 2014) - Chammas, Sérgio M.; Carneiro, Sylvia M.; Ferro, Rafael S.; Antoniazzi, Marta M.; Jared, Carlos
Abstract In this study, the development of integument and cutaneous glands in the toad Rhinella granulosa (Bufonidae) at different larval stages and in postmetamorphic and adult forms was examined. The analyses were conducted using histological, ultrastructural and morphometric methods. The results showed that cellular aggregations of precursor epidermal glands start to appear in stage 31 of (Herpetologica, 16, 1960 and 183) and then proliferate and invade the dermis. After stage 41, granular and mucous glands are very similar to those found in adults. The granular glands are syncytial and are surrounded by a distinct layer of myoepithelial cells. In the region of parotoid macroglands, the granular glands accumulate and their alveoli progressively increase until they reach adult size. An analysis by scanning electron microscopy showed the inner distribution of the syncytial nuclei and the myoepithelial cells. The morphological changes observed in the integument of tadpoles are associated with the gradual adaptation to terrestrial environments by preparing the individual for future chemical defence against predators and micro‐organisms.